Jellies and other ocean drifters - Shelley, Mark ([S.l.] : Sea Studios Production, 1996)
Highlight on delicate jellies trailing long tentacles, predator comb jellies, web-weaving larvaceans, colonial salps and 30-foot long siphonophores
Monteray Bay Aquarium in collaboration with The Monterey Bay Aquarium
Executive producer, Nora L. Deans ; writer, Robin Burnett ; editor, Glen Ebesu
Narrator: Leonard Nimoy
Keywords: Jelly